PENGARUH AUDIT QUALITY TERHADAP PREDIKSI LABA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2021-2023) - Sri Aulia Ramaddini Utami; Tarmizi Achmad (Diponegoro Journal of Accounting, 2025)
This study aims to examine and analyze the effect of audit quality on earnings prediction. Audit quality in this research is measured using three indicators, namely the size of the Public Accounting Firm (KAP), auditor industry specialization, and audit tenure as independent variables, with earnings predictability as the dependent variable. In addition, this study employs Return on Assets (ROA) and Profit or Loss as control variables to strengthen the robustness of the results. The population consists of all banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The samples were selected using a purposive sampling method, resulting in 141 observations. Data analysis was carried out using multiple regression models.The results indicate that the size of the Public Accounting Firm has a positive and significant effect on earnings prediction, suggesting that companies audited by Big Four firms tend to have more reliable financial statements for forecasting future earnings. In contrast, auditor industry specialization and audit tenure were found to have no significant effect on earnings prediction.